Nigerian surgical outcomes – Report of a 7-day prospective cohort study and external validation of the African surgical outcomes study surgical risk calculator. (August 2019) - Osinaike, Babatunde; Ayandipo, Omobolaji; Onyeka, Tonia; Alagbe-Briggs, Olubusola; Mohammed, Alhassan; Oyedepo, Olanrewaju; Nuhu, Ahmed; Asudo, Felicia; Akanmu, Olanrewaju; Nwokorie, Chris; Mohammed, Abdulrahman; Edubio, Mark; et al.
Abstract: Background: Surgical outcomes study for individual nations remains important because of international differences in patterns of surgical disease. We aimed to contribute to data on post-operative complications, critical care admissions and mortality following elective surgery in Nigeria and also validate the African Surgical Outcomes Study (ASOS) surgical risk calculator in our adult patient cohort. Materials and methods: We conducted a 7-day, national prospective observational cohort study in consented consecutive patients undergoing elective surgery with a planned overnight hospital stay following elective surgery during a seven-day study period. The outcome measures were in-hospital postoperative complications, critical care admissions and in-hospital mortality censored at 30 days. Also, we identified variables which significantly contributed to higher ASOS surgical risk score. External validation was performed using area under the receiver operating characteristic curve (ROC) for discrimination assessment and Hosmer–Lemeshow test for calibration. Results: A total of 1, 425 patients from 79 hospitals participated in the study. Postoperative complications occurred in 264(18.5%, 95% CI 16.6–20.6), 20(7.6%) of whom were admitted into the ICU and 16(6.0%) did not survive. Total ICU admission was 57 (4%), with mortality rate of 23.5% following planned admission and overall in-hospital death was 22(1.5%, 95% CI 0.9–2.2). All prognostic factors in the ASOS risk calculator were significantly associated with higher ASOS score and the scoring system showed moderate discrimination (0⋅73, 95% CI 0.62–0.83). Hosmer–Lemeshow χ2 test revealed scale was well calibrated in the validation cohort. Conclusion: NiSOS validates the findings of ASOS and the ability of the ASOS surgical risk calculator to predict risk of developing severe postoperative complications and mortality. We identified failure-to-rescue as a problem in Nigeria. Furthermore, this study has provided policy makers with benchmarks that can be used to monitor programmes aimed at reducing the morbidity and mortality after elective surgery. We recommend the adoption of the ASOS surgical risk calculator as a tool for risk stratification preoperatively for elective surgery. Highlights: First to report the incidence of postoperative complications, ICU admission and death after elective surgery in Nigeria. First African study to externally validate the African Surgical Outcomes Study (ASOS)surgical risk calculator. Surgical outcomes in Nigeria is consistent with the findings of the African Surgical Outcomes Study (ASOS). The ASOS surgical risk calculator predicts risk of developing severe postoperative complications and death.